Digital Search Behaviour and Hedonic Well Being: and SOR and U&G Approach in Indonesian Higher Education: Digital Search Behaviour and Hedonic Well Being: and SOR and U&G Approach in Indonesian Higher Education - Rini Larasati Irawan (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
This study aims to examine the relationship between Indonesian students’ digital search behavior on Google Trends and their hedonic well-being within higher education. Moving beyond traditional survey-based research, it employs big data analytics to capture real-time behavioral dynamics. Google Trends (Google LLC), Pytrends Python library (Python Software Foundation), Stata (StataCorp), EVIEWS (IHS Global Inc.), VAR/VECM models, Granger causality, Impulse Response Function, Forecast Error Variance Decomposition, reliability checks through repeated pulls, normalization via anchoring, supplemented by literature review and secondary survey sources. Data extracted from Google Trends via Pytrends were normalized and repeatedly pulled for consistency. Using VAR/VECM, Granger causality, IRF, and FEVD in Stata and EVIEWS, results show scholarship and tuition fee searches dominate, underlining financial priorities. Mental health searches fluctuate sharply, peaking during COVID-19, while happiness searches remain low yet dynamic. Statistical tests confirm financial and psychological searches significantly affect hedonic well-being. The research develops the Hedonic Well-Being Search Index (HWSI) and integrates the Stimulus–Organism–Response (SOR) and Uses & Gratifications (U&G) frameworks into higher education marketing. It pioneers the use of search analytics as a real-time proxy for student well-being and decision-making in the Indonesian context.